Effects of foliar spraying ABA on ultrastructure and photosynthesis of cotton leaves at bolling stage - CHENG Guo; ZHAO Xiushuai; YIN Zi; WANG Xingpeng; HE Shuai (Xibei zhiwu xuebao)
[Objective] The study aims to investigate the mechanism of different concentrations of abscisic acid (ABA) on the photosynthetic effect and ultrastructure of cotton leaves during the bolling stage, and provide a theoretical basis for the regulation of cotton ineffective water loss by ABA in southern Xinjiang. [Methods] Cotton ‘Tahe No. 2’ cultivated in Alar of Xinjiang was sprayed with water (control) and ABA at low concentration (50 μmol/L) and high concentration (100 μmol/L). Photosynthetic pigment content, gas exchange parameters, stomatal characteristics and ultrastructure of leaves were determined. [Results] Compared with the control, after ABA spraying for 1 d, the stomatal density, shape index, chloroplast area, and water use efficiency of cotton leaves were increased, while the chlorophyll content, net photosynthetic rate, and transpiration rate were decreased. The effect of the high concentration treatment was more obvious. After ABA spraying for 4 d, the stomatal density of cotton leaves treated with a high concentration was decreased and the shape index was increased, while that of low concentration treatment was increased. The chloroplasts in the cells of cotton leaves treated with ABA were neatly arranged and compact, but the number of chloroplasts was decreased. The starch grains in the chloroplasts under high ABA treatment became larger. [Conclusion] Foliar spraying of ABA reduces stomatal opening, chlorophyll content, photosynthetic efficiency, and transpiration rate, and increases chloroplast area and perimeter in cotton leaves. High concentration treatment is more effective in reducing the ineffective water loss and enhancing water use efficiency in cotton.